THE THEMATIC AND IDEOLOGICAL WORLD OF SHODMON SULAYMON’S POETRY (American Journal of Pedagogical and Educational Research, 2026)
This scientific article analyzes the artistic and aesthetic features of the poetry of Shodmon Sulaymon, one of the talented representatives of modern Uzbek literature. The research examines the thematic scope, ideological direction, and poetic interpretation methods of the poet’s works from a scientific perspective. In particular, the article analyzes the artistic expression of themes such as love, homeland, humanity, spirituality, and historical memory in the poet’s creative works. The main features of Shodmon Sulaymon’s lyrics, including sincerity, emotional depth, symbolic imagery, and poetic expressive means, are considered separately. The formation of lyricism in the poet’s works, the philosophical interpretation of the concept of love, and the role of national and historical motives in his poetic heritage are analyzed based on scientific sources. According to the results of the research, Shodmon Sulaymon’s poetry is evaluated as an important poetic phenomenon in modern Uzbek literature that promotes spiritual purity, artistic sincerity, and moral values.